2014
DOI: 10.1002/lary.24914
|View full text |Cite
|
Sign up to set email alerts
|

Detection of otoacoustic emissions in chinchilla when the middle ear contains amniotic fluid

Abstract: Both human amniotic fluid and saline in the chinchilla middle ear resulted in changes in otoacoustic-emission detection patterns and WBR that may be relevant to newborn hearing screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…1 for ER) at frequencies below 1 kHz. In the publication by Akinpelu et al (2015), the EA of normal chinchillas ranged from 0.2–0.4 (0.6–0.8 for ER) at f < 1 kHz. In our present study, the ambient EA of control ears at low frequencies ranged from 0.4–0.8, much larger values than those in the other studies.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…1 for ER) at frequencies below 1 kHz. In the publication by Akinpelu et al (2015), the EA of normal chinchillas ranged from 0.2–0.4 (0.6–0.8 for ER) at f < 1 kHz. In our present study, the ambient EA of control ears at low frequencies ranged from 0.4–0.8, much larger values than those in the other studies.…”
Section: Discussionmentioning
confidence: 98%
“…These investigators also reported the ER in neonatal and adult chinchillas (Hsu et al 2001). Akinpelu et al (2015) compared ambient ER of normal chinchillas with those injected with middle ear fluid. In the present study, the pattern of our EA tympanograms in uninfected normal ears is consistent with those reported by Margolis et al (2001) and Hsu et al (2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations